Pengaruh Kecerdasan Interpersonal dan Tanggung Jawab terhadap Kepercayaan Diri Siswa Kelas V SD Negeri se-Kecamatan Maesan Kabupaten Bondowoso - Mohammad Ali Akbar (Jurnal Gentala Pendidikan Dasar, 2023)
This study aims to determine the significance of the influence of interpersonal intelligence and responsibility partially or simultaneously on self-confidence. This research used a quantitative approach with the type of ex-post facto research. The population of this research is 629 students of the fifth-grade elementary schools in Maesan District with 245 students as research sample which determined by The Slovin Formula. Data collection techniques used a psychological scale was tested on 150 students. The analysis prerequisite test includes the normality test used the Kolmogorov-Smirnov method, linearity test, multicollinearity test, and heteroscedasticity test. Hypothesis test used multiple linear regression analysis technique. The results of the analysis show that 1) interpersonal intelligence partially had a significant effect on self-confidence with an effective contribution of 14.22%; 2) partial responsibility had a significant effect on self-confidence with an effective contribution of 25.98%; and 3) interpersonal intelligence and responsibility simultaneously had a significant effect on self-confidence with a simultaneous contribution of 40.2%.